2009
DOI: 10.1242/dev.037440
|View full text |Cite
|
Sign up to set email alerts
|

Lrp6-mediated canonical Wnt signaling is required for lip formation and fusion

Abstract: Neither the mechanisms that govern lip morphogenesis nor the cause of cleft lip are well understood. We report that genetic inactivation of Lrp6, a co-receptor of the Wnt/β-catenin signaling pathway, leads to cleft lip with cleft palate. The activity of a Wnt signaling reporter is blocked in the orofacial primordia by Lrp6 deletion in mice. The morphological dynamic that is required for normal lip formation and fusion is disrupted in these mutants. The expression of the homeobox genes Msx1 and Msx2 is dramatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
180
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 142 publications
(194 citation statements)
references
References 54 publications
9
180
1
4
Order By: Relevance
“…Liu and Millar (2010) reported that the dynamic activation of the WNT/beta-catenin signaling pathway was correlated with the occurrence of a cleft lip and cleft palate. Song et al (2009) reported that cleft lip with cleft palate may be induced by genetic inactivation of Lrp6, a co-receptor of the WNT/beta-catenin signaling pathway. A previous case-control study associated mutations in AXIN2, a gene belonging to the WNT signaling pathway, with the occurrence of cleft lip/palate (Letra et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Liu and Millar (2010) reported that the dynamic activation of the WNT/beta-catenin signaling pathway was correlated with the occurrence of a cleft lip and cleft palate. Song et al (2009) reported that cleft lip with cleft palate may be induced by genetic inactivation of Lrp6, a co-receptor of the WNT/beta-catenin signaling pathway. A previous case-control study associated mutations in AXIN2, a gene belonging to the WNT signaling pathway, with the occurrence of cleft lip/palate (Letra et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…23 Pregnant dams were injected intraperitoneally with 200 mg/kg/day LiCl or the control NaCl solution on E8.5 to E11.5. The embryonic kidneys were dissected out at E12.5 for subsequent experiments.…”
Section: Maternal Administration Of Lithium Chloridementioning
confidence: 99%
“…Levels of mRNAs were normalized to glyceraldehyde-3-phosphate dehydrogenase (Gapdh) to allow comparisons among different experimental groups using the DCt method. 23 Chromatin Immunoprecipitation and Luciferase Reporter Assay…”
Section: Rna Isolation and Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, mutations in VANGL1 have been associated with neural tube defects (Kibar et al, 2009;Kibar et al, 2007b). There is also an essential role for canonical Wnt signaling in the closure of the neural tube, palate, ventricular septum and ventral fissure of the eye, based on the phenotype of LDL-receptor related protein 6 (Lrp6) mutant mice (Pinson et al, 2000;Song et al, 2009;Song et al, 2010). It is not known whether this dependence on the canonical Wnt pathway principally reflects a requirement for rapid cell proliferation.…”
Section: Introductionmentioning
confidence: 99%